Efficacy and tolerability of methotrexate at a dose of 15 mg/week and 10 mg/week in patients with pulmonary sarcoidosis - V.K. Gavrysyuk; I.O. Merenkova; G.L. Gumeniuk; N.V. Pendalchuk; N.D. Morska; N.A. Vlasova (Medičnì Perspektivi)
The objective of this study is to conduct a comparative study of the efficacy and safety of methotrexate (MT) at a dose of 10 mg/week and 15 mg/week in patients with pulmonary sarcoidosis having contraindications to GCS therapy. Material and Methods. The study involved 44 patients with stage II pulmonary sarcoidosis (26 females and 18 males aged 24 to 70) with contraindications to the appointment of therapy glucocorticosteroid (GCS). In group 1 (28 patients), methotrexate was prescribed at a dose of 10 mg/week, in group 2 (16 patients), methotrexate was prescribed at a dose of 15 mg/week. The diagnosis and assessment of the dynamics of sarcoidosis were carried out taking into account clinical symptoms based on the results of high-resolution computed tomography and body plethysmography. The significance of differences in indicators was determined using the Student's t-test and Fisher's exact test. The number of cases of clinical treatment without residual changes of a fibrous nature in the lung parenchyma in patients after treatment with methotrexate at a dose of 15 mg/week significantly increased compared to the same indicator in the group of patients after treatment at a dose of 10 mg/week (81.3% and 42.4% respectively, p=0.025). An increase in the therapeutic dose of methotrexate from 10 mg/week to 15 mg/week leads to a decrease in the time to achieve a clinical cure (10.1±0.5 months and 12.8±0.8 months respectively, р˂0.02), indicating an accelerating rate of regression of sarcoidosis. Immunosuppressive therapy of patients with pulmonary sarcoidosis using the drug at doses of 10 and 15 mg/week is characterized by satisfactory tolerability.